Comparative VET European research since the 1980s : accommodating changes in VET systems and labour markets - Clarke, Linda [Verfasser]; Westerhuis, Anneke [Verfasser]; Winch, Christopher [Verfasser] (My University, 2021)
"The article assesses the role comparative research plays from the 1980s in understanding vocational education and training (VET) systems in Europe, driven by political, economic, social and labour market changes. This research has been transformed, moving from national comparisons of VET systems, grounded in institutional theory and engaging with convergence versus divergence debates or human capital theory, to the varieties of capitalism approach considering groups of countries as representative of particular capitalist economies, to transcending national boundaries and emphasising capitalist diversity, governance and labour agency. Drawing on examples of research in which the authors and others have been involved, particularly on the construction industry, the article traces this development and shows how, despite governance weaknesses, comparative research has been enriched by the addition of a European Union level through the introduction of tools, such as the European Qualifications Framework. Four dimensions are proposed – labour market, governance, education and competence – capable of identifying VET ‘families’ and intra-national variations and capturing the dynamics of VET systems. Through a multi-dimensional and multi-level framework, comparative VET research can provide a deeper understanding of how and why VET systems respond to the challenges of technological, economic and environmental change." (Author's abstract ; BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.2 Europa; 370; Vergleichende Berufsbildungsforschung; Berufsbildungssystem; Historische Entwicklung; EU-Bildungspolitik; Europäischer Qualifikationsrahmen; Europa